Electro-mechanical behaviour of graphene-based geotextiles for pavement health monitoring. Issue 2 (April 2023) - Senadheera, Harini; Deo, Ravin; Azoor, Rukshan; Bouazza, Abdelmalek; Kodikara, Jayantha
Abstract: Smart geosynthetics have attracted significant interest for potential applications in geotechnical structures owing to their conductive properties. This paper presents an analysis of the electro-mechanical response of graphene-based geotextiles for application in pavements. Experimental and numerical studies were conducted on a commercially available graphene-coated geotextile to understand its response to induced strains. The material was subjected to tensile loading with the effect of transverse strains also being tested, utilizing Digital Image Correlation (DIC). Experimental results indicated a significant electro-mechanical behaviour in the geotextile, with the relative resistance change being non-linear with applied strain. Existing analytical solutions could not predict the observed behaviour; hence, a multi-physics numerical model was developed using concepts of piezoresistivity to capture the non-linear behaviour. The numerical model was calibrated using the experimental data and then validated with experimental data from tests conducted for different specimen sizes. The model could capture the non-linear electro-mechanical behaviour and the electrical response due to axial and transverse strains in the material. This study is expected to serve as a basis for using graphene-based geotextiles for structural health monitoring (SHM) purposes in geotechnical structures, such as in roads. Highlights: Smart geosynthetics have become increasingly popular in pavement health monitoring. A graphene-based geotextile was assessed for potential road sensing applications. Experimental testing was conducted to evaluate its electro-mechanical response. A multi-physics numerical model was developed to capture the observed piezoresistive behaviour. The model was validated with experimental data obtained for varying specimen sizes.